Pengaruh Dosis Pupuk Silika terhadap Pertumbuhan dan Hasil Tiga Varietas Kacang Hijau (Vigna radiata) - Nurwendah, Miftah Azzura; Koentjoro, Yonny; Suhardjono, Hadi (BIOEDUSCIENCE, 2025)
Background: Mung beans (Vigna radiata) are one of the plants cultivated in Indonesia because they have many benefits, so cultivating green beans can be a profitable prospect. The use of superior varieties can increase better production results, in addition to the use of additional fertilizer besides basic fertilizer. Silica fertilizer is a fertilizer that has benefits for improving harvest quality, strengthening plant stems, etc. This study examined by 2 treatments: the dose of silica and 3 types of mung bean plant varieties, which aiming to identify the interaction and the right combination between the dose of silica fertilizer and superior varieties of mung beans to produce better production results. Method: This study was using a two-factorial completely randomized design. The first factor is silica dosage (Si0 : 0cc/l; Si1 : 1cc/l; Si2 : 2cc/l; and Si3 : 3cc/l) and the second factor is mung bean variety (V1 : Vima-1; V1 : Vima-2 ; and V1: Kutilang). Results: The results of the study revealed that Si2V2 treatment is the most effective to increase the production of green bean plants. Conclusion: The applications of silica fertilizer and superior varieties of mung beans had a significant impact on the observed parameters and the best results combination was revealed in the Si2V2 treatment (Silica 2cc and Vima-2).